2020
DOI: 10.1038/s41419-020-2360-0
|View full text |Cite|
|
Sign up to set email alerts
|

TRPC6-dependent Ca2+ signaling mediates airway inflammation in response to oxidative stress via ERK pathway

Abstract: Ozone (O 3) plays an extremely important role in airway inflammation by generating reactive oxygen species (ROS) including hydrogen peroxide, then promoting redox actions and causing oxidative stress. Evidences indicate that TRPC6 (canonical transient receptor potential channel 6) is a redox-regulated Ca 2+ permeable nonselective cation channel, but its role in the setting of oxidative stress-related airway inflammation remains unknown. Here, we found that both TRPC6 −/− mice and mice pretreated with SAR7334, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 52 publications
(65 reference statements)
1
25
0
Order By: Relevance
“…Oxidative stress induces TRPC6 expression and function in podocytes ( 36 ), HEK293T cells ( 37 ), vascular myocytes ( 38 ), neutrophils ( 35 ), and macrophages ( 39 ). In a recent study, TRPC6 in bronchial epithelium cells, was shown to act as an oxidative stress sensor where the TRPC6-mediated calcium cascade leads to the activation of the extracellular signal-regulated kinase (ERK) pathway and inflammation ( 40 ). This could be a possible inflammatory response pathway in several cell types in response to ozone, but this has yet to be described in COPD.…”
Section: Mechanisms Of Ozone-induced Oxidative Stress On Inflammationmentioning
confidence: 99%
“…Oxidative stress induces TRPC6 expression and function in podocytes ( 36 ), HEK293T cells ( 37 ), vascular myocytes ( 38 ), neutrophils ( 35 ), and macrophages ( 39 ). In a recent study, TRPC6 in bronchial epithelium cells, was shown to act as an oxidative stress sensor where the TRPC6-mediated calcium cascade leads to the activation of the extracellular signal-regulated kinase (ERK) pathway and inflammation ( 40 ). This could be a possible inflammatory response pathway in several cell types in response to ozone, but this has yet to be described in COPD.…”
Section: Mechanisms Of Ozone-induced Oxidative Stress On Inflammationmentioning
confidence: 99%
“…TRPC6 is also expressed in PSCs, where it mediates hypoxia-induced migration and production of cytokines ( Nielsen et al, 2017 ). In a mouse model, it could be shown that inhibition of TRPC6 with specific antagonists (SAR7334, BI-749327) diminishes the inflammatory response in the lungs and ameliorates cardiac and renal fibrosis ( Lin et al, 2019 ; Chen et al, 2020 ). One can presume that such a beneficial effect could also be elicited in PDAC, in part by inhibiting neutrophil recruitment into the tumor.…”
Section: Immunity and Pdacmentioning
confidence: 99%
“…Evidence shows that TRPC6 is a crucial regulator of inflammatory cascades, especially in pulmonary inflammation (Chen et al, 2020 ; Ortiz-Muñoz et al, 2020 ). TRPC6 contributes to platelet activation, leukocyte transendothelial migration, lung vascular barrier disruption, and airway inflammation (Tauseef et al, 2012 ; Weber et al, 2015 ; Chen et al, 2020 ; Ortiz-Muñoz et al, 2020 ). In addition, activation of the TRPC6 channel promotes apoptosis in neonatal glomerular mesangial cells and renal tubular epithelial cells under different injury conditions (Soni and Adebiyi, 2016 ; Hou et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%